CT Attenuation Analysis of Carotid Intraplaque Hemorrhage - Saba, L.; Francone, M.; Bassareo, P.P.; Lai, L.; Sanfilippo, R.; Montisci, R.; Suri, J.S.; De Cecco, C.N.; Faa, G. (American Journal of Neuroradiology, 2018)
BACKGROUND AND PURPOSE: Intraplaque hemorrhage is considered a leading parameter of carotid plaque vulnerability. Our purpose was to assess the CT characteristics of intraplaque hemorrhage with histopathologic correlation to identify features that allow for confirming or ruling out the intraplaque hemorrhage.MATERIALS AND METHODS: This retrospective study included 91 patients (67 men; median age, 65 ± 7 years; age range, 41–83 years) who underwent CT angiography and carotid endarterectomy from March 2010 to May 2013. Histopathologic analysis was performed for the tissue characterization and identification of intraplaque hemorrhage. Two observers assessed the plaque's attenuation values by using an ROI (≥ 1 and ≤2 mm2). Receiver operating characteristic curve, Mann-Whitney, and Wilcoxon analyses were performed.RESULTS: A total of 169 slices were assessed (59 intraplaque hemorrhage, 63 lipid-rich necrotic core, and 47 fibrous); the average values of the intraplaque hemorrhage, lipid-rich necrotic core, and fibrous tissue were 17.475 Hounsfield units (HU) and 18.407 HU, 39.476 HU and 48.048 HU, and 91.66 HU and 93.128 HU, respectively, before and after the administration of contrast medium. The Mann-Whitney test showed a statistically significant difference of HU values both in basal and after the administration of contrast material phase. Receiver operating characteristic analysis showed a statistical association between intraplaque hemorrhage and low HU values, and a threshold of 25 HU demonstrated the presence of intraplaque hemorrhage with a sensitivity and specificity of 93.22% and 92.73%, respectively. The Wilcoxon test showed that the attenuation of the plaque before and after administration of contrast material is different (intraplaque hemorrhage, lipid-rich necrotic core, and fibrous tissue had P values of .006, .0001, and .018, respectively).CONCLUSIONS: The results of this preliminary study suggest that CT can be used to identify the presence of intraplaque hemorrhage according to the attenuation. A threshold of 25 HU in the volume acquired after the administration of contrast medium is associated with an optimal sensitivity and specificity. Special care should be given to the correct identification of the ROI.Azarea under the receiver operating characteristic curveCEAcarotid endarterectomyHUHounsfield unitIPHintraplaque hemorrhageLRNClipid-rich necrotic core